МЕТОДЫ СТРАТЕГИЧЕСКОГО УПРАВЛЕНИЯ ПЕРСОНАЛОМ В КРУПНЫХ ХОЛДИНГАХ И КОРПОРАЦИЯХ (Journal of Economic Research & Business Administration, 2015)
An important task of economic science is the creation of effective governance mechanisms adequate to the requirements of a market economy. Currently, one of the major problems for Kazakh enterprises is a creation of a system of personnel management methods that could ensure the production of competitive products and could solve social problems, which in turn would create the preconditions for each industry to correspond to the levels existing in 50 most competitive countries in the world. This level of development of the system of personnel management methodshas been defined by the President of Kazakhstan as the country's main development priority until 2015.